Observation of Duration-Tunable Soliton Explosion in Passively Mode-Locked Fiber Laser - Pan Wang; Xiaosheng Xiao; Hang Zhao; Changxi Yang (IEEE Photonics Journal, 2017)
We report on the first observation, to the best of our knowledge, of soliton explosions in an ultrafast fiber laser mode-locked by nonlinear polarization evolution. The soliton explosion is a transition state between stable mode-locking and noise-like pulses regimes. By tuning the waveplates and the spectral filter, the duration of soliton explosions is widely tunable from ∼100 roundtrips to thousands of roundtrips. Our experimental results together with the numerical simulations reveal the dissipative nature of soliton explosions, and may be beneficial for further understanding of this striking phenomenon.